Liver Fibrosis in Alcoholic Liver Disease - Bataller, Ramon; Gao, Bin (Seminars in Liver Disease, 2015)
Excessive alcohol consumption causes a wide spectrum of liver disease, ranging from simple steatosis to severe forms of liver injury such as steatohepatitis, liver fibrosis, cirrhosis, and liver cancer. Moreover, alcohol consumption also accelerates liver fibrosis in patients with other types of liver diseases such as viral hepatitis and nonalcoholic fatty liver disease. Virtually all clinical complications of alcoholic liver disease occur in patients with established fibrosis and cirrhosis, thus making fibrosis a key parameter for treatment and prognosis of patients. Here, the authors review diagnosis, management, and antifibrotic therapy of alcoholic liver fibrosis. They discuss both the unique features of alcoholic liver fibrosis and the similarities to liver fibrosis from other etiologies, and review molecular pathogenesis and animal models. Finally, future directions for basic and clinical research on alcoholic liver fibrosis are proposed.
Keywords: alcoholic hepatitis; hepatic stellate cells; steatohepatitis; animal models